2017
DOI: 10.33160/yam.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Initial Results of Robotic Surgery for Primary Lung Cancer: Feasibility, Safety and Learning Curve

Abstract: Background At the end of 2016, robot-assisted thoracoscopic surgery (RATS) was still not covered by Japanese national health insurance. Therefore, few institutions in Japan perform RATS and even fewer have reported procedures as they occurred earlier. So, we decided to focus on the initial results of RATS for primary lung cancer. Methods We retrospectively reviewed 44 patients who underwent RATS for primary lung cancer from January 2011 to August 2016. After mastering the initial procedure, we introduced a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In various studies, the investigators reported that the operation time for lobectomy was between 104 and 226 minutes after the learning curve. The same time was 136.9 minutes in our study, which was consistent with the results of the published studies [13][14]. The curve representing the operation time of the first 20 patients showed a statistically significant decline ( Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…In various studies, the investigators reported that the operation time for lobectomy was between 104 and 226 minutes after the learning curve. The same time was 136.9 minutes in our study, which was consistent with the results of the published studies [13][14]. The curve representing the operation time of the first 20 patients showed a statistically significant decline ( Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…15 In regards to the surgeons' prior operative experience, the present study found no differences in the incidence of major postoperative complications for ≤ 20 cases versus > 20 cases, although the former group were associated with longer operative duration, similar to other contemporary reports. 24 Limitations of the present multi-institutional study included its retrospective nature, and the intrinsic potential biases and data heterogeneity associated with this study design. All the participating centers had a prospectively maintained database, and a standardized data form with a data dictionary were formulated after discussion and consensus a priori to centralized data collection.…”
Section: Discussionmentioning
confidence: 97%
“…However, no significant trend in the reduction in the RATS operative times, when comparing the first 10 with the last 10 cases, was observed in Worrell's series 32 . We calculated the learning curve regarding operation time from 13 articles, 24,32,33,49,59,66‐73 and the pooled data indicated that the operative time decreased significantly as the surgeon performed more surgeries (254.9 vs 198.7 min, WMD: 56.95, 95% CI:30.06‐83.83, P < .001; Supporting Information Figure S3). Therefore, it is possible that with the popularization of RATS, RATS would show a comparable operative time with VATS.…”
Section: Discussionmentioning
confidence: 97%